Synthesis and Antimicrobial Evaluation of 6-Alkylamino-N-phenylpyrazine-2-carboxamides - Servusova-Vanaskova, Barbora; Paterova, Pavla; Garaj, Vladimir; Mandikova, Jana; Kunes, Jiri; Naesens, Lieve; Jílek, Petr; Dolezal, Martin; Zitko, Jan (Chemical biology & drug design, 2015)
This work presents synthesis and antimicrobial evaluation of nineteen 6-alkylamino-N-phenylpyrazine-2-carboxamides. Antimycobacterial activity was determined against Mycobacterium tuberculosis H37Rv, M. kansasii and two strains of M. avium. Generally, the antimycobacterial activity increased with prolongation of simple alkyl chain and culminated in compounds with heptylamino substitution (3e, 4e) with MIC = 5-10 μm against M. tuberculosis H37Rv. On the contrary, derivatives with modified alkyl chain (containing e.g. terminal methoxy or hydroxy group) as well as phenylalkylamino derivatives were mainly inactive. The most active compounds (with hexyl to octylamino substitution) were evaluated for their in vitro activity against drug-resistant strains of M. tuberculosis and possessed activity comparable to that of the reference drug isoniazid. None of the tested compounds were active against M. avium. Some derivatives exhibited activity against Gram-positive bacteria including methicillin-resistant Staphylococcus aureus (best MIC = 7.8 μm), while Gram-negative strains as well as tested fungal strains were completely unsusceptible. Active compounds were tested for in vitro toxicity on various cell lines and in most cases were non-toxic up to 100 μm.
Keywords: multidrug-resistant strains; Methicillin-Resistant Staphylococcus aureus; Cell Line; simulace molekulového dockingu; antiinfekční látky; Chemistry Techniques, Synthetic; Mycobacterium tuberculosis; Anti-Infective Agents; Antifungal Agents; Microbial Sensitivity Tests; Molecular Docking Simulation; cytotoxicity; antibacterial evaluation; pyrazinamide derivatives; preklinické hodnocení léčiv; Antitubercular Agents; zvířata; vztahy mezi strukturou a aktivitou; Humans; techniky syntetické chemie; methicilin rezistentní Staphylococcus aureus; Drug Evaluation, Preclinical; buněčné linie; mikrobiální testy citlivosti; Structure-Activity Relationship; antimycobacterial evaluation; lidé; antifungální látky; antituberkulotika; Animals